Case report: Coexistence of sigmoid tumor with unusual pathological features and multiple colorectal neuroendocrine tumors with lymph node metastases - Pang, Shu; Song, Jiugang; Zhang, Kun; Wang, Jia; Zhao, Haiying; Wang, Yongjun; Li, Peng; Zong, Ye; Wu, Yongdong (Frontiers in Oncology, 2023)
The coexistence of adenocarcinoma and neuroendocrine neoplasm (NEN) in the same tumor is rare. What is rarer is that the neuroendocrine component is well-differentiated neuroendocrine tumor (NET) Grade (G) 1. Most colorectal NETs are single; multiple neuroendocrine tumors (M-NETs) are rare. Well-differentiated NET rarely metastasizes. Here, we present a unique case of synchronous sigmoid tumor and multiple colorectal NETs with lymph nodes metastases. The sigmoid tumor consisted of adenocarcinoma and NET G1. The metastatic component was NET G1. A 64-year-old man underwent colonoscopy for persistent changes in bowel habits and positive fecal occult blood for 1 year. An ulcerative lesion, which was diagnosed as colon cancer, was seen in the sigmoid colon. In addition, scattered raised lesions can be seen in the colon and rectum. Surgical resection was performed for him. Pathological findings suggested that the ulcerative lesion was composed of 80% adenocarcinoma and 20% neuroendocrine component (NET G1), while the remaining lesions were consistent with NET G1. At the same time, 11 lymph nodes around the resected intestinal segment were invaded by NET G1. The prognosis of the patient was good. After 13 months follow-up, no recurrence and metastasis were found. We hope to provide a reference and improve understanding of the clinic-pathological features and biological behavior of these unique tumors. We also aim to emphasize the importance of radical surgery and individualized treatment.